2021
DOI: 10.15642/ijet2.2021.10.1.86-98
|View full text |Cite
|
Sign up to set email alerts
|

What to Accommodate to Develop Students' Academic Writing? Need Analysis for a Research-Based Textbook Development

Abstract: The development of research-based learning proliferates throughout the world, and it depicts the growth of an academic article's publication globally. To strengthen the paper's quality, particularly in Indonesia, the students need a guideline on writing an academic article. This qualitative and quantitative research would portray the needs analysis in developing a research-based textbook in academic writing. Fifty students and thirty lecturers were involved in the interview, documentation, and survey. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Such findings support the claim made by Bandura based on the social cognitive theory that self-efficacy has a significant function in predicting writing performance. For example, the study by Safriyani et al (2021) stated that there were nine materials for assessing the ability to write academic articles.…”
Section: Skills That Are Considered To Determine the Quality Of Writi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Such findings support the claim made by Bandura based on the social cognitive theory that self-efficacy has a significant function in predicting writing performance. For example, the study by Safriyani et al (2021) stated that there were nine materials for assessing the ability to write academic articles.…”
Section: Skills That Are Considered To Determine the Quality Of Writi...mentioning
confidence: 99%
“…This literature review process is a long process of searching for gaps and research novelties where the author is obliged to find the essence of the novelty of the research. One aspect that causes students' low grades is mastering grammar (Safriyani et al, 2021). It is shown that almost all the examples presented in the discussion section at the beginning contain grammatical errors.…”
Section: Skills That Are Considered To Determine the Quality Of Writi...mentioning
confidence: 99%
“…Academic plagiarism is conducted with different methods such as: copy and paste, translation from other languages, translation and back translation, manipulation of the text with paraphrasing, style modification, self-plagiarism, plagiarism of ideas, or a combination of them [11], [12].…”
Section: Introductionmentioning
confidence: 99%